2005
DOI: 10.1111/j.1365-2869.2005.00461.x
|View full text |Cite
|
Sign up to set email alerts
|

Noradrenergic, serotonergic and GABAergic antagonists injected together into the XII nucleus abolish the REM sleep‐like depression of hypoglossal motoneuronal activity

Abstract: SUMMAR Y Recently, we reported that the suppression of hypoglossal (XII) motoneuronal activity that occurs during the carbachol-induced, rapid eye movement (REM) sleep-like state is abolished by the microinjection into the XII nucleus of a drug mix that antagonizes aminergic excitation and amino acid-mediated inhibition (prazosin, methysergide, bicuculline and strychnine). We now assess the role of glycinergic inhibition in the depression of XII motoneuronal activity and estimate the distribution of the antago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
65
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 51 publications
2
65
2
Order By: Relevance
“…Catecholaminergic neurons in A1/C1, A5, A7, and to a lesser extent locus ceruleus, innervate upper airway motoneurons (Rukhadze and Kubin, 2007). Noradrenergic innervation of upper airway motoneurons contributes to activation of upper airway dilator motoneurons (Lai et al, 2001;Fenik et al, 2005;Chan et al, 2006;Rukhadze and Kubin, 2007). However, in our studies, at least the A5 and A7 groups appear relatively unperturbed by hypoxia/reoxygenation exposures.…”
contrasting
confidence: 49%
“…Catecholaminergic neurons in A1/C1, A5, A7, and to a lesser extent locus ceruleus, innervate upper airway motoneurons (Rukhadze and Kubin, 2007). Noradrenergic innervation of upper airway motoneurons contributes to activation of upper airway dilator motoneurons (Lai et al, 2001;Fenik et al, 2005;Chan et al, 2006;Rukhadze and Kubin, 2007). However, in our studies, at least the A5 and A7 groups appear relatively unperturbed by hypoxia/reoxygenation exposures.…”
contrasting
confidence: 49%
“…Second, extracellular levels of NE are reduced in the HMN during induced PS-like atonia (Lai et al, 2001). Finally, injection of the selective a 1 -adrenoceptor antagonist prazosin into the HMN reduces HMN nerve activity in urethane-anaesthetized rats (Fenik et al, 2005a). Recently, it has been shown that, in freely behaving rats, microdialysis application of terazosin, an a 1 -and a 2B -adrenoceptor antagonist, to the HMN reduces both respiratoryrelated and tonic GG activities during W, whereas application of phenylephrine, a specific a 1 -adrenoreceptor agonist, increases GG muscle activity during W and SWS, but not during PS (Chan et al, 2006).…”
Section: Ne and Gg Muscle Activitymentioning
confidence: 96%
“…After completion of the 15-min observation period following the last PE injection and an additional interval of 37 Ϯ 4 (SD) min, PZ was injected successively at three sites (40 nl each) targeting the XII nucleus at three rostrocaudal levels to antagonize ␣ 1-adrenoceptors in the entire XII nucleus in 10 shamand 7 CIH-treated rats. The first injection was placed at the same coordinates used for the PE injections, followed by one injection 0.65 mm caudal and one injection 0.65 mm rostral to the first one (14,15). The three PZ injections were completed within 8.0 Ϯ 0.5 (SE) min.…”
Section: Animals and Administration Of Cihmentioning
confidence: 99%